ANALISIS PREDIKSI KEBANGKRUTAN DAN HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN BATU BARA - Augustpaosa Nariman (Jurnal Riset Akuntansi dan Keuangan, 2016)
This study aims to examine and analyze the bankruptcy prediction on coal mining company listed onthe Indonesia Stock Exchange. Bankruptcy prediction on coal mining companies using the Altman ZScore to see how big a bankruptcy prediction coal mining company. The data used in this study arethe financial statements of coal mining companies that are in the period 2012-2014 on the IndonesiaStock Exchange. The analysis technique used is a bankruptcy prediction model Altman Z-Score usingfive variables representing liquidity ratios, profitability ratio, and activity ratio. During theobservation period of 2012-2014 shows that the research data as many as 19 coal mining companiesthere are in a state of bankruptcy. In 2012 and 2013 there were 31.6% of companies experiencingbankruptcy prediction, and 26.32% are in the gray area. 2014 showed an increase where there are42.10% of companies experiencing bankruptcy prediction and 5.26% in the gray area..Keywords: Altman Z-Score, Predicted Bankruptcy, Stock price